A STUDY ON THE MANAGEMENT OF DIRECT SELLING BUSINESS (AMWAY INDIA LTD) IN ASSAM: A CASE STUDY OF JORHAT DISTRICT OF ASSAM - Dr. Horen Goowalla (International Journal of Research Science and Management, 2015)
India is a major hub for most of the direct selling companies in the world and is going to be one of the biggest market in the world as population is one of the major factor for the growth of the industry. Direct Selling in India as of 2014 has a size of Rs 7200 crore as announced in the seminar “DIRECT 2014” by FICCI (Federation of Indian Chambers of Commerce and Industry).In this seminar,there were talks between the government and the direct selling committee of India to have a distinct law and clarification for the Direct Selling Industry in India like the other advance countries of the world. Amway India has nation wide presence with over 142 offices; 4 regional mother warehouses and 55 city warehouses. The distribution and home delivery network set up with the support of independent logistics partners caters to over 11500 zip codes across the country. It has also become one of the largest FMCG ( Fast Moving Consumer Goods ) company in India after crossing the revenue of big FMCG firms such as Emami, P&G, Gillette India. An attempt has been made to highlight the impact of direct selling companies in Assam. and study the present and upcoming marketing trends of the direct selling companies in the study area and offer suggestive measure in order to improve the direct selling in the study area.